Asthma, Food Allergy, and How They Relate to Each Other - Foong, Ru-Xin; du Toit, George; Fox, Adam T. (Frontiers in Pediatrics, 2017)
It is well known that there is a link between atopic conditions and that having one atopic condition can predispose to the development of others. The association between asthma and food allergy has been well researched over the years; although the exact interplay between the two atopic conditions remains to be fully understood. Food allergic infants are at increased risk for the development of asthma and are at risk of food-induced asthmatic episodes but also anaphylaxis. Having a diagnosis of both food allergy and asthma has also been shown to have an effect on the severity of a patient’s disease including being at greater risk of severe asthmatic episodes. Therefore, it is important for clinicians to understand the relationship between these two conditions in order to treat and manage these children safely.